Analysis of influencing factors xiaomi mobile phone repurchase decisions - Surya Safa'at, Refa; Mayla, Mayla Surveyandini (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to determine and analyze the influence of brand image, features and price perceptions on the decision to repurchase Xiomi cellphones by students at Wijayakusuma University. The analysis technique used in this research is multiple linear regression analysis with the help of SPSS software. Based on the results of multiple linear regression analysis, the regression equation is obtained, namely Y = 0.163 + 0.262X1 + 0.615X2 + 0.209X3 + e. The calculated F value obtained was 44.474 > F table 2.70, meaning that the regression model was declared suitable for use in estimating the population. From the results of data analysis it can be obtained that (1) Brand image has a positive and significant influence on repurchase decisions, (2) Features have a positive and significant influence on repurchase decisions, (3) Price perception has a positive and significant influence on repurchase decisions.